The effect of different coupling agent on zeolite modification for development of polyetehersulfone mmms for O2/N2 separation - Nik Nur Zanaryah, Nik Hassan (2012)
The industrial gas separations have been attracted in using membrane for gas separations since membrane separation technologies have the advantages of energy efficiency, simplicity and low cost.This lead to the exploration mixed matrix membrane (MMMs) that combining the polymeric membrane filled with organics particles.In order to improve the interaction between polymer and zeolite,chemical modification on the surface of zeolite using silane coupling agents need to be done to increase the compatibility between zeolite and polymer.In this study,the effect of difference coupling agents used on zeolite modification in development of Polyethersulfone MMMs for O2/N2 separation was studied. Three types of coupling agents were used which are 3-aminopropyltriethoxysilane,glycidoxypropyltrimethoxysilane and aminopropyltriethoxysilane (APTMOS).The polymer solution was prepared contains of 30% Polyethersulfone (PES) as the polymer, 55% of N-Methyl Pyrolidone (NMP) as the solvent and 15% of zeolite 5A.The dry/wet phase inversion method was used to produce the membrane.The membrane was coated with silicone and n-hexane in order to decrease the surface defect and tested using O2 and N2 gases to determine the membrane performance.For surface and cross section image of membrane were identified using Scanning Electron Microscope (SEM).Membrane was also characterized using Fourier Transform Infrared Spectroscopy (FTIR) to analyze the presence of silane coupling agent functional group.As a conclusion,the best performance was identified by using glycidoxypropyltrimethoxysilane which gives high selectivity about 3.14.